Investigation of Corrosion Behaviour of Aluminium Alloy Subjected to Laser Shock Peening without a Protective Coating. (6th December 2015) - Trdan, U.; Grum, J.
Abstract : The effect of shock waves and strain hardening of laser shock peening without protective coating (LSPwC) on alloy AA 6082-T651 was investigated. Analysis of residual stresses confirmed high compression in the near surface layer due to the ultrahigh plastic strains and strain rates induced by multiple laser shock waves. Corrosion tests in a chloride environment were carried out to determine resistance to localised attack, which was also verified on SEM/EDS. OCP transients confirmed an improved condition, that is, a more positive and stable potential after LSPwC treatment. Moreover, polarisation resistance of the LSPwC treated specimen was by a factor of 25 higher compared to the untreated specimen. Analysis of voltammograms confirmed an improved enhanced region of passivity and significantly smaller anodic current density of the LSPwC specimen compared to the untreated one. Through SEM, reduction of pitting attack at the LSPwC specimen surface was confirmed, despite its increased roughness.